Faktor – Faktor yang Mempengaruhi Keputusan Siswa dalam Memilih Lembaga Kursus Bahasa Inggris (Studi Pada The Benefit English Course) - Dewi Nova Sapira (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
The large number of institutions in the English village of Pare means that The Benefit English Course institution must market its English language course institution services well. Promotion via Instagram social media can develop business and have an attractive influence on prospective new students. Decisions regarding prices will also determine the success of the course institution. Not only that, Word of Mouth also plays a big role in forming an effective marketing communication strategy for The Benefit English Course institution. The purpose of this research is to determine whether there is an influence that Social Media Instagram (X1), Price Perception (X2), and Word of Mouth (X3) have on students' decisions to choose The Benefit English Course (Y) course institution simultaneously. This research method used was quantitative using a sample of 139 students at The Benefit English Course during February - July 2022. The data was analyzed using a multiple regression analysis test with the equation Y = 3.683 + 0.230 X1 + 0.355 X2 + 0.301 Social Media Instagram (X1), Price Perception (X2), and Word Of Mouth (X3) have a positive relationship with purchasing decisions (Y). The results of the t test and F test also show that the significance value of the Social Media Instagram (X1), Price Perception (X2) and Word of Mouth (X3) variables is smaller than 0.050 and the R square value is 0.924 so it can be concluded that the Social Media Instagram variable ( X1), Price Perception (X2) and Word of Mouth (X3) have a significant influence on the Purchasing Decision (Y) Students of the Benefit English Course Course Institution and have an influence of 70.7%.